KULTUR KELUARGA ISLAM DENGAN FENOMENA PERNIKAHAN DIBAWAH UMUR (Studi Kasus di Desa Pai Kecematan Wera Kabupaten Bima) - Ifan; Jainuddin; Syarif Hidayatullah (LPPM STAI Muhammadiyah Probolinggo, 2025)
In addition to exploring the impact of Islamic family culture on the societal phenomena of underage marriage, this research seeks to ascertain the legal ramifications of making underage marriages lawful. This research takes a descriptive qualitative tack, gathering information by methods such as participant observation, in-depth interviews, and document reviews. The study's findings show that underage marriage in PAI Village, Wera District, Bima Regency, is a multi-faceted issue affected by many economic, social, cultural, and legal viewpoints. This practice has multidimensional impacts, including the breakdown of education, economic hardship, and health risks for mothers and babies. A holistic approach that integrates economic empowerment, religious education, and changes in social norms is needed to address this issue and build a sakinah family.